Nurse Burnout in Hospice and Palliative Care: A Scoping Review. (January 2023) - Frechman, Erica; Wright, Patricia M.
Burnout in hospice and palliative care nurses is a growing issue, especially in light of the COVID-19 pandemic. However, few studies have focused specifically on burnout in this population. A scoping review was undertaken to identify what is known about burnout among hospice and palliative care nurses, and to unify disparate findings. Analysis of eight articles revealed three overarching categories: personal factors, organizational/workplace factors, and nursing professional development factors. Each category was then divided into three cross-cutting subcategories: contributory and noncontributory factors, mitigating factors, and workplace issues. Recommendations for individuals include self-care as well as self-awareness of intrinsic characteristics that can predispose one to burnout. Within the workplace, leaders are challenged to support evidence-based practice and ongoing education. Role modeling positive communication skills, effective conflict mitigation, responsiveness, promotion of equity, and workplace commitment also help to create a culture of wellness. Nursing professional development may aid in resilience-building, and promotion of self-efficacy, self-confidence, and assertiveness. Although all identified recommendations were derived from the literature, no interventional studies have been conducted to test the effects of suggested interventions. Future research should include interventional studies as well as qualitative research to capture nuanced experiences of burnout in hospice and palliative care nurses.